BaZrO3 refractory crucibles for vacuum induction melting of industrial Zr-based bulk metallic glass master alloys with Y addition. Issue 8 (July 2022) - Chen, Guangyao; Yu, Feihai; Hou, Xiao; Liu, Jian; Yang, Yuchen; Wang, Enhui; Feng, Qisheng; Duan, Baohua; Lu, Xionggang; Hou, Xinmei; Li, Chonghe
Abstract: The absence of appropriate melting method and expensive cost of high-purity Zr raw material limit the commercial application of Zr-based bulk metallic glass. In the present study, using high oxygen industrial grade sponge Zr as raw material and the metal Y as additive, the low-cost and high-purity master alloys were successively prepared using a VIM method with a BaZrO3 refractory crucible. The results indicate that the BaZrO3 refractory exhibited good erosion resistance to the alloy melt, the Y additive formed the Y2 O3 barrier layer on the surface of crucible, which prevented the melt permeation into the crucible, then effectively reduced the thickness of the erosion layer. In addition, the metal Y deoxidizer could remove the oxygen of melts, finally the low oxygen Zr-based master alloy (about 0.02 wt%) was prepared. These results may provide a promising preparing technique prototype of low-cost Zr-based bulk metallic glass.